A minimalist furan–maleimide AB-type monomer and its thermally reversible Diels–Alder polymerization. Issue 51 (10th May 2016) - Lacerda, Talita M.; Carvalho, Antonio J. F.; Gandini, Alessandro
Abstract : An original approach to prepare and polymerize the shortest Diels–Alder AB monomer. Abstract : The present study reports an easy and direct route for the synthesis of highly pure 2-furfurylmaleimide, a minimalist furan–maleimide AB-type monomer, which was used for the preparation of a rigid thermally reversible polymer based on the Diels–Alder reaction. This strategy has high potential for the development of novel polymers and copolymers mainly derived from renewable resources.